2009
DOI: 10.1097/md.0b013e318194da65
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis Caused by Staphylococcus aureus

Abstract: Staphylococcus aureus is the leading cause of infectious endocarditis and its mortality has remained high despite better diagnostic and therapeutic procedures over time. We conducted a retrospective review of 133 cases of definite S. aureus endocarditis seen at a single tertiary care hospital over 22 years to assess changes in the epidemiology and incidence of the infection, manifestations, outcome, risk factors for mortality, and impact of cardiac surgery on prognosis.Patients were classified into 2 groups: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 193 publications
3
42
3
Order By: Relevance
“…Cases of health care-associated IE were more likely to be caused by S. aureus (125,133,142). Thus, in contrast to previous IE series where S. aureus comprised Ͻ10% of cases (71,145), S. aureus is now consistently the cause of IE in Ͼ25% of cases (125)(126)(127)(128)(129)146). …”
Section: Epidemiologycontrasting
confidence: 46%
See 4 more Smart Citations
“…Cases of health care-associated IE were more likely to be caused by S. aureus (125,133,142). Thus, in contrast to previous IE series where S. aureus comprised Ͻ10% of cases (71,145), S. aureus is now consistently the cause of IE in Ͼ25% of cases (125)(126)(127)(128)(129)146). …”
Section: Epidemiologycontrasting
confidence: 46%
“…Several studies have concluded that all patients with S. aureus prosthetic valve IE, regardless of whether they have complications, benefit from surgery, citing the lower mortality rates found with the combination of medical and surgical treatments (146,152,153,183,(229)(230)(231)(232). For example, Fernandez Guerrero et al found that of the 65% of patients who underwent valve replacement surgery, only 15% died, whereas all of the 35% of patients who did not receive surgery died (146).…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations